The impact of environmental factors on performances during the World Orienteering Championships - Herbert-Losier, K.; Platt, S.; Hopkins, W. G. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Research in high-performance orienteering has primarily addressed physical and cognitive aspects, although many environmental factors might impact performance, such as race course characteristics. For interpreting magnitudes of environmental effects on race outcomes as being small, moderate, large, and very large; 0.3, 0.9, 1.6, and 2.5 of the typical within-athlete race-to-race variation may be used. Furthermore, improvements equal to 0.3 of this typical variation represent the smallest worthwhile enhancement in performance (SWEP). Here, we examined environmental effects and SWEP in relation to World Orienteering Championships performances from 2006-2013. Mixed-linear modelling was applied to the finishing times of sprint, middle, and long distance events, considering the effects of race length, distance climbed, number of controls, home advantage, venue identity, athlete identity, and residuals. Within-athlete variability was lower in the finals (coefficient of variation, mean ± SD; 4.9 ± 1.4%) than qualifiers (7.3 ± 2.4%), with the SWEP ranging from 1.0 to 3.2%. Home advantage was clearly beneficial in most events (up to -5.5%), as were the between-venue differences in performance times. Adding climb particularly impacted sprint performances. As greater familiarity with the terrain likely mediated the home advantage, foreign athletes would benefit from training in nations hosting the World Orienteering Championships for familiarization. Our results also suggest that elite orienteers should focus on interventions entailing improvements of at least 1% for SWEP. The greater within-athlete variability in competitive orienteering versus other sports is likely due to outcomes depending on both physical (running) and mental (navigational) skills.